ANALISIS DETERMINAN TERHADAP PERUBAHAN HARGA SAHAM PERUSAHAAN PERBANKAN KONVENSIONAL DI BURSA EFEK INDONESIA - Abdurrafi Murtanto (2023)
The purpose of this study to determine the effect of conventional banking company shares prices listed on the Indonesia Shares Exchange (IDX) with factors originating from external and internal companies. The external factors used are inflation and interest rates, while factors i from internal companies use profitability and liquidity which are proxied by Return on Assets (ROA) and Loan to Deposit Ratio (LDR). This research is a quantitative research with secondary data. The objects used as this research are conventional banking companies listed on the Indonesia Shares Exchange (IDX) in the period 2017 - 2021. The sampling technique uses purposive sampling which obtains 38 companies as samples that match the specified criteria. This study uses annual data for a 5 year period which produces 190 research data. The data processing method used in this study is the panel data regression model with the help of EViews - 12 as a data processing tool. The result of this study is that inflation has no significant effect on shares prices in a negative or opposite direction. Interest rates and liquidity (LDR) have no significant effect on shares prices in a positive or unidirectional direction. Meanwhile, profitability (ROA) has a significant influence on shares prices in a positive or unidirectional direction.